2017
DOI: 10.1007/s12551-017-0367-2
|View full text |Cite
|
Sign up to set email alerts
|

Gliadins from wheat grain: an overview, from primary structure to nanostructures of aggregates

Abstract: Gliadins are well-known wheat grain proteins, particularly important in food science. They were studied as early as the 1700s. Despite their long history, it has been difficult to identify their higher-order structure as they aggregate in aqueous solution. Consequently, most studies have been performed by extracting the proteins in 70% ethanol or dilute acidic solutions. The carboxy-terminal half of α-and γ-gliadins have α-helix-rich secondary structures stabilized with intramolecular disulfide bonds, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 48 publications
4
55
0
Order By: Relevance
“…Optical, fluorescent, and TEM microscope observations showed that PT-gliadin can form sticky and large extra-cellular aggregates, as already reported [ 28 ]. This biochemical property can be explained by the presence of glutamine and proline-rich repetitive regions in the N-terminal of gliadin protein.…”
Section: Discussionsupporting
confidence: 83%
“…Optical, fluorescent, and TEM microscope observations showed that PT-gliadin can form sticky and large extra-cellular aggregates, as already reported [ 28 ]. This biochemical property can be explained by the presence of glutamine and proline-rich repetitive regions in the N-terminal of gliadin protein.…”
Section: Discussionsupporting
confidence: 83%
“…Its biocompatibility, hydrophobicity, and ability to modify and enhance drug release profile make it a potential drug carrier [7]. Furthermore, use of gliadin in medical scaffolds, nanofibers, films, and micro and nanoparticles showed adequate stability and flexibility [8][9][10][11]. Gliadin nanoparticles (GNPs) have been formulated for their applications in sustained drug release for various drugs including meletin, amoxicillin, polymethoxyflavons, resveratrol, paclitaxel, and carbazole [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…After immunoblotting, membranes were pre-incubated in blocking buffer only or blocking buffer containing plasma. In the immunoblot, bands are visible in the 30-40 kDa range corresponding to various α/β and γ gliadins (Figure 8) (44). These gliadin bands are less visible over the course of 2-fold dilutions.…”
Section: Resultsmentioning
confidence: 99%